Sosialisasi Pendewasaan Usia Perkawinan Sebagai Pencegahan Stunting Oleh Mahasiswa KKN Kolaboratif Kelompok 188 di SMP 3 Ledokombo Desa Sumbersalak Kecamatan Ledokombo Kabupaten Jember - Prasetya, Chandra Wahyu; Amiruddin, Naufal; Rafikri, Rizky Maulana; Suwae, Grace Rita Rovina; Sari, Anggita; Safitri, Adisty Bella; Pasaribu, Jhon Feliks (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Stunting is a disease that affects children's brain and physical growth as a result of a long-term lack of proper nutrition. The lack of nutritional intake that children receive is caused by a lack of knowledge and unpreparedness of parents in caring for their children. This is related to the rise of early marriage which occurs as a result of various factors, one of which is the mindset of the people who consider early marriage to be commonplace, especially for rural communities. To support the reduction of stunting due to early marriage, the students carried out an outreach on maturing the age of marriage which was carried out targeting students of SMP Negeri 3 Ledokombo. This activity aims to make students understand the importance of maturity and careful preparation before deciding to go through with marriage. This counseling will give birth to prospective parents with adequate knowledge in parenting, which in turn will also have a contribution to preventing the birth of stunted children. The author concludes, this activity is very relevant to the problem of stunting faced in Wonorejo Village, where the many cases of early marriage experienced by students of SMP Negeri 3 Ledokombo are the main factors that increase the stunting rate in the area.